Feasibility study of first-line chemotherapy using Pemetrexed and Bevacizumab for advanced or recurrent nonsquamous non-small cell lung cancer in elderly patients: TORG1015 - Kozuki, Toshiyuki (BMC Cancer, 2016)
BACKGROUND: The addition of bevacizumab to cytotoxic agents prolongs survival in patients with nonsquamous non-small cell lung cancer (NSCLC). To date, there is no evidence to suggest that treatment with a cytotoxic agent plus bevacizumab is more effective than a cytotoxic agent alone for nonsquamous NSCLC in elderly patients. We conducted a feasibility study of pemetrexed plus bevacizumab as a first-line treatment for advanced or recurrent nonsquamous NSCLC in elderly patients. METHODS: Major eligibility and exclusion criteria included: chemotherapy-naive status; non-fitness for bolus combination chemotherapy; stage III/IV or relapsed nonsquamous NSCLC; age ≥70; performance status 0–1; absence of brain metastasis; and no history of hemoptysis and thoracic irradiation. Pemetrexed (500 mg/m(2)) and bevacizumab (15 mg/kg) were administered intravenously on day 1, and repeated every 3 weeks thereafter. The primary endpoint was safety, and the secondary endpoints were objective response rate (ORR), progression-free survival (PFS), overall survival (OS), and the percentage of patients who completed ≥3 cycles. RESULTS: From October 2010 to April 2012, a total of 12 patients were enrolled. No dose-limiting toxicity or treatment-related deaths were observed. Three patients achieved PR, and the ORR was 25 %. The median PFS and OS were 5.4 months (95 % CI 1.1–8.8 months) and 13.6 months (95 % CI 5.3–15.6 months), respectively. Seven of 12 patients (58 %) received ≥3 cycles. CONCLUSIONS: Pemetrexed plus bevacizumab in the treatment of elderly patients with nonsquamous NSCLC was well tolerated and shows promise as first-line treatment. TRIAL REGISTRATION: UMIN Clinical Trial Registry; UMIN000004263. Registered on 25 September, 2010.